Gadolinium sesquisulfide anchored N-doped reduced graphene oxide for sensitive detection and degradation of carbendazim. (June 2022) - Yogesh Kumar, K.; Prashanth, M.K.; Parashuram, L.; Palanivel, Baskaran; Alharti, Fahad A.; Jeon, Byong-Hun; Raghu, M.S.
Abstract: Agriculture is having a major role in solving issues associated with food shortages across the globe. Carbendazim (CZM) is one of the fungicides which is commonly used in agriculture to grow crops in large quantities and fast. Monitoring CZM content is in high demand for environmental remediation. The present work deals with the synthesis of gadolinium sesquisulfide anchored Nitrogen-doped reduced graphene oxide (Gd2 S3 /NRGO) through a simple microwave-assisted method. X-ray diffraction and morphological studies confirm the formation of the nanocomposite. Gd2 S3 /NRGO showed enhanced activity both in electrochemical detection and light-driven degradation of CZM compared to Gd2 S3 and NRGO. Gd2 S3 /NRGO modified glassy carbon electrode (GCE) exhibit a wide linear range of 0.01–450 μM CZM with 0.009 μM LOD using differential pulse voltammetry (DPV). Gd2 S3 /NRGO@GCE showed good selectivity, stability, and recovery (98.13–99.10%) in the river water sample. In addition, Gd2 S3 /NRGO has been explored towards the visible-light-induced degradation of CZM. The reactions conditions were optimized to achieve maximum efficiency. 94% of CZM was degraded within 90 min in presence of Gd2 S3 /NRGO. Mechanism of electrochemical redox reaction and degradation of CZM in presence of Gd2 S3 /NRGO has been explored to the maximum extent possible. Degradation intermediates were identified using LC-MS. Graphical abstract: Image 1 Highlights: Microwave assisted synthesis of orthorhombic Gd2 S3 /NRGO. Decrease in the bandgap of Gd2 S3 upon NRGO decoration. Gd2 S3 /NRGO@GCE detects a wide range of carbendazim (0.01–450 μM). Efficient degradation of CZM under visible light (94%). Gd2 S3 /NRGO@GCE exhibited good sensitivity, selectivity and stability.